Jenis-jenis Cacing Tanah (Oligochaeta) yang Terdapat di Kawasan Cagar Alam Lembah Anai Sumatera Barat - Syami Nilawati; - Dahelmi; Jabang Nurdin (Universitas Andalas, 2014)
A study on the earthworms (Oligochaeta) at Lembah Anai Nature Reserve, West Sumatera has been conducted from February to May, 2013. The purpose of this study was to identify earthworms species at the Nature Reserve. The earthworms were collected from different altitudinal levels ranged from 400 to 800 m above sea level using hand sorting method. There were three species of earthwoms found; Pontoscolex corethrurus (Glossoscolecidae), Pheretima posthuma and Megascolex kempi (Megascolecidae) these three species belong to sub order Neooligochaeta. All species were found at all altitudinal level.Keywords: Earthworm (Oligochaeta), Hand sorting, Lembah Anai